Analisis Kelayakan Finansial Usaha Pengolahan Sagu di Desa Walasolo Kecamatan Asera Kabupaten Konawe Utara - Asnani, Asnani; Surni, Surni; Saediman, Haji (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This study aims to first find out how the sago processing process carried out by CV. Karmila in Walasolo Village, Asera District, North Konawe Regency, secondly, the financial feasibility of the sago processing business CV. Karmila in Walasolo Village, Asera Subdistrict, North Konawe Regency. The analysis used in this study is a financial feasibility analysis consisting of Net Present Value (NPV), Net Benefit-Cost Ratio (NBCR), Internal Rate of Return (IRR), Payback period (PBP), Break-Even Point (BEP) and Analysis Sensitivity. The results of this study indicate that the processing of sago in a CV. Karmila is still simple even though the processing has used a grater, senso, and water machine. While in terms of the feasibility of sago business CV. Karmila is worth trying. Because the discount factor (df) of 12% obtained an NPV value of Rp 210,604,893, NBCR of Rp 1.90, an IRR of 29.28%, PBP, 2.44 Years or 29 months 28 days with a business life of 5 years, and results of calculation of BEP company CV. Karmila must get a turnover of Rp. 258,853,495. Whereas the sensitivity feasibility analysis where if the condition of the increase in production costs is 10% at a discount factor (df) of 6%, the NPV value of Rp. 50 months 4 days. Whereas the condition if the selling price decreases, the NPV is IDR 55,898,480, NBCR is 1.23IRR of 21.50% and PBP is 3.00 years or 36 months. Under these circumstances, the sago business CV. Karmila is still worth the effort.